2022
DOI: 10.1039/d1na00684c
|View full text |Cite
|
Sign up to set email alerts
|

Surface ligand chemistry on quaternary Ag(InxGa1−x)S2 semiconductor quantum dots for improving photoluminescence properties

Abstract: Ternary and quaternary semiconductor quantum dots (QDs) are candidates for cadmium-free alternatives. Among these, semiconductors containing elements from groups 11, 13, and 16 (i.e., I–III–VI2) are attracting increasing attention since...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…The enhancement of PL QY appeared to result from the interaction of the GaS x shell with the Lewis acidic In( iii ) species, which could passivate the unsaturated sulfur sites on the surface of the metal chalcogenide semiconductors. 42…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhancement of PL QY appeared to result from the interaction of the GaS x shell with the Lewis acidic In( iii ) species, which could passivate the unsaturated sulfur sites on the surface of the metal chalcogenide semiconductors. 42…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement of PL QY appeared to result from the interaction of the GaS x shell with the Lewis acidic InIJIII) species, which could passivate the unsaturated sulfur sites on the surface of the metal chalcogenide semiconductors. 42 Subsequently, the aforementioned two samples [with uncontrolled (1.8) and controlled pH (3.3)] were subjected to encapsulation by the InMOFs. In both cases, the pale orange powder was obtained after the QDs/InIJNO 3 ) 3 mixture solution was mixed with a solution of fumaric acid, indicating the formation of InMOFs under both pH conditions, as will be mentioned later using XRD patterns and TEM images.…”
Section: Encapsulation Of Qds In Inmofsmentioning
confidence: 99%
“…For example, we have recently found that the use of Zn compounds for the surface treatment improves PL intensity, but it was accompanied by a substantial increase in defect-related emission. 57 When the mixing ratio to QDs was fixed at 0.05:0.05 in EML3, the PL QY was 32% and the fraction of band-edge emission was 82%. The PL decay profiles for the EMLs and the corresponding lifetime components are shown in Figure S2 and Table S1.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, manipulation of the ligand shell can improve the PL properties of these QDs as demonstrated by Chevallier et al, who achieved a significant PL QY enhancement by capping quaternary ZAIS QDs with trioctylphosphine . Also, Z-type ligands such as metal halides like ZnCl 2 can effectively passivate dangling bonds on AgIn x Ga 1– x S 2 QDs, leading to a 3-fold increase of PL QY . Recently, also the organic-to-aqueous phase transfer of ZAIS QDs was assessed by NMR spectroscopy for the hydrophilic ligands 11-mercapto­undecanoic acid, DHLA, and cysteine, and the efficiency of the ligand exchange and its influence on the PL QY were determined .…”
Section: Introductionmentioning
confidence: 99%
“…12 Also, Z-type ligands such as metal halides like ZnCl 2 can effectively passivate dangling bonds on AgIn x Ga 1−x S 2 QDs, leading to a 3-fold increase of PL QY. 49 Recently, also the organic-to-aqueous phase transfer of ZAIS QDs was assessed by NMR spectroscopy for the hydrophilic ligands 11mercaptoundecanoic acid, DHLA, and cysteine, and the efficiency of the ligand exchange and its influence on the PL QY were determined. 50 Other studies of ligand exchange procedures for ternary or quaternary QDs focus on the impact of this exchange on QD performance in applications such as hydrogen production, 16 optoelectronic devices, 13,15,51 and bioimaging.…”
Section: ■ Introductionmentioning
confidence: 99%